Osteosarcoma Cell‐Derived Migrasomes Promote Macrophage M2 Polarization to Aggravate Osteosarcoma Proliferation and Metastasis - Wanshun Liu; Lei Li; Xiaoming Bai; Mengxue Zhang; Wei Lv; Yongbin Ma; Yuzhi Sun; Hongjing Zhang; Qing Jiang; Qingqiang Yao; Zhi‐Yuan Zhang (Advanced Science)
Abstract The local tumor microenvironment (TME) of osteosarcoma (OS) includes several tumor niches that control tumor growth and cell extravasation. Migrasomes are recently discovered extracellular vesicles produced during cell migration. Herein, the results show OS cell production of migrasomes in vivo and in vitro. Osteosarcoma cell‐derived migrasomes (OCDMs) aggravate OS proliferation and metastasis, and impeding OCDM formation alleviates the malignant progression of OS. Further studies revealed that migrasome‐associated nanoparticles (MANPs) are the functional unit of OCDMs and that OCDMs promote M2 polarization of macrophages in the TME in a MANPs‐dependent manner. Moreover, milk fat globule‐EGF factor 8 (MFGE8) in OCDMs is identified as a key protein that enhances phagocytosis to promote the M2 polarization of macrophages. Overall, the results reveal that OCDMs enhance the M2 polarization of macrophages in the TME to aggravate OS progression via MFGE8. These findings may guide the development of OCDM‐modulating OS therapies.